Mikroblog – odmiana blogu czy oddzielny gatunek? - Szews, Przemysław (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
A microblog is a common concept in the new media framework. There is still no precise definition of the microblog or an answer to the question whether it is a variety of blog or a separate genre. Communication within micro-blogging is limited, which is why characteristic acronyms, language structures and vocabulary were developed. Websites like Twitter are used in politics, journalism and marketing. These websites are often a valuable source of information and the fastest information transmission channel for journalists. The microblog shares some features with the blog, but differences between them are visible: the microblog is not so thematically restricted, it has its own individual style and informative and communicative function, and it is more interactive and more frequently updated. According to such communication features, it is possible to define it as a new, separate internet genre.